The adventures of Huckleberry Finn - Twain, Mark, 1835-1910; Seelye, John D; Cardwell, Guy, 1905-2005 (New York : Penguin Books, 2009)
A feisty young boy fakes his own death to escape his abusive father and heads off down the Mississippi River with his newfound friend Jim, a runaway slave
"First published In Great Britain by Chatto & Windus 1884. First published in the United States of America by Charles L. Webster and Co., 1885"--T.p. verso
"Edition with an introduction by John Seelye published in Penguin Books (U.K.) 1985. Published in Penguin Books (U.S.A.) 1986. Edition with notes by Guy Cardwell [first] published in Penguin Books (U.S.A.) 2003"--T.p. verso
Includes bibliographical references (p. [xxxi]-xxxiii)
Keywords: Finn, Huckleberry -- (Fictitious character) -- Fiction; Runaway children -- Fiction; Male friendship -- Fiction; Fugitive slaves -- Fiction; Race relations -- Fiction; Boys -- Fiction; Mississippi River -- Fiction; Missouri -- History -- 19th century -- Fiction; Adventure stories; Adventure fiction; Humorous fiction; Bildungsromans